Significantly enhanced second-harmonic generations with all-dielectric antenna array working in the quasi-bound states in the continuum and excited by linearly polarized plane waves - Han Zhanghua (Nanophotonics, 2020)
The recently emerging all-dielectric optical nanoantennas based on high-index semiconductors have proven to be an effective and low-loss alternative to metal-based plasmonic structures for light control and manipulations of light–matter interactions. Nonlinear optical effects have been widely investigated to employ the enhanced interactions between incident light and the dielectrics at the Mie-type resonances, and in particular magnetic dipole resonances, which are supported by the semiconductor. In this paper, we explore the novel phenomenon of bound states in the continuum supported by high-index semiconductor nanostructures. By carefully designing an array of nanodisk structures with an inner air slot as the defect, we show that a novel high quality-factor resonance achieved based on the concept of bound state in the continuum can be easily excited by the simplest linearly polarized plane wave at normal incidence. This resonance further enhances the interactions between light and semiconductors and boosts the nonlinear effects. Using AlGaAs as the nonlinear material, we demonstrate a significant increase in the second-harmonic generation efficiency, up to six orders of magnitude higher than that achieved by magnetic dipole resonances. In particular, a second-harmonic generation efficiency around 10% can be numerically achieved at a moderate incident pump intensity of 5 MW/cm2.